2007
DOI: 10.1097/coc.0b013e3180337792
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Calcitonin Gene-Related Peptide (CGRP) in Breast Carcinogenesis and Its Correlation With 99mTc-(V)DMSA Scintimammography

Abstract: CGRP expression and neoangiogenesis are intensified in mixed invasive-preinvasive breast lesions; an underlying relation may exist, requiring further investigation. CGRP also appears associated with 99mTc-(V)DMSA's propensity to depict preinvasive pathologies. This relationship could denote an additional proliferative role for CGRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…S1 A), VEGF may work as a downstream molecule. These results were consistent with the previous reports using human HaCaT keratinocytes (19) and breast cancer cells (20). In the present experiment, we can also show that CGRP exerts a crucial action in enhancement of angiogenesis ( Figs.…”
Section: Expressions Of Growth Factors In Tumor Stromal Tissues In Cgrp-supporting
confidence: 83%
See 1 more Smart Citation
“…S1 A), VEGF may work as a downstream molecule. These results were consistent with the previous reports using human HaCaT keratinocytes (19) and breast cancer cells (20). In the present experiment, we can also show that CGRP exerts a crucial action in enhancement of angiogenesis ( Figs.…”
Section: Expressions Of Growth Factors In Tumor Stromal Tissues In Cgrp-supporting
confidence: 83%
“…It was reported that a neuropeptide, substance P, had a proangiogenic activity (18), although the details of the mechanism of this proangiogenic activity were not studied precisely. It was reported that CGRP regulates the expression of VEGF in human HaCaT keratinocytes by activation of ERK1/2 MAPK (19) and that CGRP expression and neoangiogenesis are intensified in mixed invasive-preinvasive breast lesions of carcinoma (20). These suggested that CGRP may regulate tumor-associated angiogenesis.…”
mentioning
confidence: 94%
“…CGRP influences normal breast development [10][11][12][13] and mammary blood flow by vasodilatation and can induce breast angiogenesis, exerting its activity in the earlier stages of malignant transformation [13,14]. Recently, its potential role in breast carcinogenesis as a mitogenic and angiogenic factor has begun to be investigated [15]. The participation of CGRP in breast carcinogenesis in relation to mammographic density has not yet been explored.…”
Section: Introductionmentioning
confidence: 98%
“…Pentavalent technetium-99m dimercaptosuccinic acid [ 99m Tc(V)DMSA] is a well-known tumor-seeking agent and an excellent indicator of cell proliferation [16][17][18][19][20] and focal adhesion kinase (FAK) activation, not only in invasive breast tumors but also in pre-invasive (DCIS), premalignant, and even histologically normal breast tissues which are at an activated status (FAK phosphorylation) to progress into malignancies [15,16]. CGRP expression and 99m Tc(V)DMSA activity were correlated in the precocious steps of breast carcinogenesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated CGRP expression has been identified in both plasma and tumours from specific cancers; including small cell lung carcinomas (Kelley et al 1994), prostate cancer (Suzuki et al 2006), breast cancer (Papantoniou et al 2007(Papantoniou et al , 2010 and thyroid cancer (Pacini et al 1991(Pacini et al , 1992. In prostate cancer, serum CGRP correlated with high-grade/stage disease (Suzuki et al 2006), however, hormone replacement therapy may interfere with CGRP's use as a diagnostic marker (Suzuki et al 2009).…”
Section: Cgrp In Cancermentioning
confidence: 99%